Differentiated instruction in a data-based decision-making context. Issue 1 (2nd January 2018) - Faber, Janke M.; Glas, Cees A. W.; Visscher, Adrie J.
ABSTRACT: In this study, the relationship between differentiated instruction, as an element of data-based decision making, and student achievement was examined. Classroom observations ( n = 144) were used to measure teachers' differentiated instruction practices and to predict the mathematical achievement of 2nd- and 5th-grade students ( n = 953). The analysis of classroom observation data was based on a combination of generalizability theory and item response theory, and student achievement effects were determined by means of multilevel analysis. No significant positive effects were found for differentiated instruction practices. Furthermore, findings showed that students in low-ability groups profited less from differentiated instruction than students in average or high-ability groups. Nevertheless, the findings, data collection, and data-analysis procedures of this study contribute to the study of classroom observation and the measurement of differentiated instruction.